(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
1C: Accounting is a digital accounting software that plays a crucial role in the digital economy by enabling efficient financial management for businesses. This article explores the features, benefits, and impact of 1C: Accounting in the context of the digital economy. It highlights its role in streamlining financial processes, improving accuracy, and enhancing decision-making. The article also discusses the importance of data security and compliance when utilizing accounting software in the digital era.